Strengthening Financial Performance of Local Governments through Internal Supervision and Accountability - Kusuma, Guan; Tenripada; Furqan, Andi Chairil; Kamase, Haryono Pasang (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study investigates the influence of the Government Internal Supervisory Apparatus (APIP) and the Government Agency Performance Accountability System (SAKIP) on the financial performance of local governments in Indonesia. Financial performance is measured through indicators of independence and sustainability, reflecting regional capacity in managing fiscal resources effectively. Using panel data from 2019–2021 with 1,623 observations across provincial, district, and city governments, multiple linear regression analysis was conducted. The results indicate that APIP significantly enhances financial performance through stronger internal control and accountability mechanisms. SAKIP also contributes positively by fostering transparent and result-oriented management. Both variables collectively strengthen fiscal independence and sustainability, confirming that internal supervision and accountability are crucial for sustainable local financial governance.